Governance for Development Political and Administrative Reforms in Bangladesh - Islam, S. Nazrul; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
Good governance is now widely recognized as the most important factor for successful development. Bangladesh has done well in terms of economic growth and diversification and various social goals, such as the Millennium Development Goals. However, it suffers from political instability and poor quality of civil administration and could grow faster with improved governance. Analyzing Bangladesh's governance problems and placing them firmly within a broader international perspective, this book makes a series of policy recommendations to improve governance for faster development; these include switching to proportional election, shortening the government-term, and rationalizing salary and size of the civil service. The book analyzes the prospects of the proposed reforms and suggests strategies for gaining support and implementing them. Although the book focuses on Bangladesh, its policy recommendations are relevant to many other developing countries.
Keywords: Asia-Politics and government; Public policy; Development economics; Economic policy; Globalization; Political science